Garbhagriha of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) is a small square chamber with entirely plain walls from the inside. It housed a stone Shiva linga (aniconic representation of Shiva). One of the sides of the garbhagriha has a stone slab designed for placing worship-related objects, while the opposite side is equipped with a pranala (water drainage).